PRINSIP DASAR PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Febriyani, Nur Amna; Hamzah, Rahma Ashari; Nurainun, Nurainun; Nurlinda, Nurlinda; Hafsah, Nur; Gedde, Rahmawati Deran (Universitas Tanjungpura, 2025)
This study aims to explore and examine in depth the fundamental principles in Indonesian language learning in elementary schools based on linguistic theory, pedagogical approaches, and national curriculum provisions. This research was carried out through a literature study method by reviewing various scientific references, including language education textbooks, articles in academic journals, and education policy documents published in the range of 2020 to 2025. The results of the analysis show that the main principles of Indonesian learning at the elementary school level include communicative, contextual, integrative, functional, and student-centered principles. These five principles emphasize the importance of a learning process that develops comprehensive language competence through authentic, interactive, and meaningful learning experiences. The implementation of these principles not only encourages students to master the structure of language, but also to understand language as a medium of thinking, creating, and interacting in social life. Thus, increasing teachers' understanding of the basic principles of Indonesian learning is a key factor in realizing an effective, fun, and consistent learning process in line with the essence of basic education.